FFT-based estimation of large motions in images: a robust gradient-based approach - Tzimiropoulos, Georgios; Argyriou, Vasileios; Stathaki, Tania (2009)
A fast and robust gradient-based motion estimation technique which operates in the frequency domain is presented. The algorithm combines the natural advantages of a good feature selection offered by gradient-based methods with the robustness and speed provided by FFT-based correlation schemes. Experimentation with real images taken from a popular database showed that, unlike any other Fourier-based techniques, the method was able to estimate translations, arbitrary rotations and scale factors in the range 4-6.